2020
DOI: 10.5937/leksir2040057k
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial and antibiofilm activity of selected polyphenolic compounds: An in vitro study on Staphylococcus aureus

Abstract: Staphylococcus aureus is a human pathogen that causes serious infections with high mortality rates. The antimicrobial activities of eight phenolic compounds (caffeic acid, chlorogenic acid, ferulic acid, morin, quercetin, isoquercitrin, rutin and hesperidin) were evaluated against planktonic and biofilm forming Staphylococcus aureus cells. Their ability to prevent biofilm formation via interference with bacterial cell adhesion and to reduce biomass of 24 h old biofilms has been addressed in this study. The ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…Contrary to the current study of isoquercitrin towards MRSA (MIC 0.5 mg/mL), a previous study has shown no inhibitory activity towards other S. aureus strains ( S. aureus Newman and S. aureus Newman Δ coa ) in concentrations up to 1024 µg/mL [ 33 ]. On the other hand, the research on S. aureus clinical isolate and S. aureus ATCC 11632 suggested its more promising antibacterial activity with MICs 0.2 mg/mL and 0.1 mg/mL, respectively [ 34 ]. The previous MIC recorded for morin was 32 µg/mL towards MRSA T144 [ 35 ], while we have highlighted it as the most active flavonoid towards MRSA, but with higher MIC compared to the previous research (125 µg/mL).…”
Section: Discussionmentioning
confidence: 99%
“…Contrary to the current study of isoquercitrin towards MRSA (MIC 0.5 mg/mL), a previous study has shown no inhibitory activity towards other S. aureus strains ( S. aureus Newman and S. aureus Newman Δ coa ) in concentrations up to 1024 µg/mL [ 33 ]. On the other hand, the research on S. aureus clinical isolate and S. aureus ATCC 11632 suggested its more promising antibacterial activity with MICs 0.2 mg/mL and 0.1 mg/mL, respectively [ 34 ]. The previous MIC recorded for morin was 32 µg/mL towards MRSA T144 [ 35 ], while we have highlighted it as the most active flavonoid towards MRSA, but with higher MIC compared to the previous research (125 µg/mL).…”
Section: Discussionmentioning
confidence: 99%
“…None of the extracts tested in this work showed activity against Staphylococcus aureus , Staphylococcus epidermidis , or Escherichia coli bacteria, although several authors have elucidated the antibacterial activity of phenolic acids, such as chlorogenic acid and caffeic acid, against these microorganisms 35 . This result can be explained by the fact that these microorganisms are highly sensitive and dependent on iron and have a mechanism to extract the compound from the host, excreting the so‐called siderophores 36 .…”
Section: Resultsmentioning
confidence: 79%
“…Staphylococcus aureus, Staphylococcus epidermidis, or Escherichia coli bacteria, although several authors have elucidated the antibacterial activity of phenolic acids, such as chlorogenic acid and caffeic acid, against these microorganisms. 35 This result can be explained by the fact that these microorganisms are highly sensitive and dependent on iron and have a mechanism to extract the compound from the host, excreting the so-called siderophores. 36 The high concentration of the compounds 2,5-DHBA, 2,4-DHBA, and 3,4-DHBA in the CG and the CS may explain these findings, since these compounds structurally resemble the bacterial siderophore, favoring the capture of iron from the medium to the bacteria, promoting the growth and resistance of these organisms.…”
Section: None Of the Extracts Tested In This Work Showed Activity Aga...mentioning
confidence: 99%
“…Gram-positive bacteria ( Staphylococcus aureus ATCC 11632 and Staphylococcus lugdunensis Ibis 2996) and Gram-negative bacteria ( Proteus vulgaris IBR P004) were examined for antibacterial activity with liposomes. The microdilution technique (96-well microtiter plates) was used to determine the minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC), as reported before [ 41 ]. The samples were placed in a tryptic soy broth (TSB) medium and infected with bacteria at a final concentration of 1 × 10 6 colony-forming units (CFU) per well.…”
Section: Methodsmentioning
confidence: 99%